Enhancing Hospitality Through Immersive Technology: The Role of Virtual Reality in Staff Training and Guest Experience - SUN, Enrique Justine (Journal Management and Hospitality, 2024)
Focusing on two main elements—staff training and guest interaction—this paper investigates the growing relevance of virtual reality (VR) in the hotel sector. As the need for creative and interesting solutions keeps growing, virtual reality (VR) becomes a great tool for staff training in real-life scenarios, including customer service, emergency response, and facilities management. Simultaneously, hotels and resorts are using virtual reality to provide possible guests interesting virtual tours of their rooms, amenities, and surrounding attractions, so impacting their choice of booking. Using guest surveys, case studies, and interviews with hotel managers, this paper uses a mixed-method approach to assess the limits and efficacy of a VR application. Studies indicate that hotel managers might use VR to improve guest satisfaction, operational effectiveness, and service quality.